Analisis kualitas pelayanan terhadap kepuasan konsumen pembeli karkas broiler di Rumah Potong Ayam (RPA) Kelurahan Kampung Mandar, Kabupaten Banyuwangi - Irvan Galantino; Budi Hartono; Eko Nugroho (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
Research was conducted at the “Kampung Mandar” broiler slaughterhouses located in Riau Street, Kampung Mandar Village, Banyuwangi District. The research aimed to determine (i) the characteristics of carcass buyers, (ii) the level of satisfaction, (iii) the quality of services provided and (iv) factors that affect carcass buyers satisfaction on broiler carcass produced by small scale chicken slaughterhouse. One hundred respondents were selected by accidental sampling method and interviewed using a structured questionnaire. Primary data were obtained from the field (from the customers and chicken slaughterhouses owners) and secondary data were obtained from Central Board Statistics, online media and local government agencies (district office). Data were analyzed using descriptive, factor analysis and multiple regression analysis. The study showed that female traders aged 41-60 years with senior high school education and earned income between IDR. 900.001-1800.000 per month represented broiler carcass buyers. Another findings showed that buyers who considered senior carcass broiler tended to rebuy the product and transferred information to others. The study also found that service quality of broiler slaughterhouse were indicated by “carcass quality assurance and skill sellers”, “response to carcass buyers” and “appropriate equipments” and these were able to increase buyers carcass satisfaction. Keywords : poultry, consumer satisfaction, factor analysis.